Global transcriptome analysis reveals extensive gene remodeling, alternative splicing and differential transcription profiles in non-seed vascular plant Selaginella moellendorffii. (January 2017) - Zhu, Yan; Chen, Longxian; Zhang, Chengjun; Hao, Pei; Jing, Xinyun; Li, Xuan
Abstract Background Selaginella moellendorffii, a lycophyte, is a model plant to study the early evolution and development of vascular plants. As the first and only sequenced lycophyte to date, the genome ofS. moellendorffii revealed many conserved genes and pathways, as well as specialized genes different from flowering plants. Despite the progress made, little is known about long noncoding RNAs (lncRNA) and the alternative splicing (AS) of coding genes inS. moellendorffii . Its coding gene models have not been fully validated with transcriptome data. Furthermore, it remains important to understand whether the regulatory mechanisms similar to flowering plants are used, and how they operate in a non-seed primitive vascular plant. Results RNA-sequencing (RNA-seq) was performed for threeS. moellendorffii tissues, root, stem, and leaf, by constructing strand-specific RNA-seq libraries from RNA purified using RiboMinus isolation protocol. A total of 176 million reads (44 Gbp) were obtained from three tissue types, and were mapped toS. moellendorffii genome. By comparing with 22, 285 existing gene models ofS. moellendorffii, we identified 7930 high-confidence novel coding genes (a 35.6% increase), and for the first time reported 4422 lncRNAs in a lycophyte. Further, we refined 2461 (11.0%) of existing gene models, and identified 11, 030 AS events (for 5957 coding genes) revealed for the first time for lycophytes. Tissue-specific gene expression with functional implication was analyzed, and 1031, 554, and 269 coding genes, and 174, 39, and 17 lncRNAs were identified in root, stem, and leaf tissues, respectively. The expression of critical genes for vascular development stages, i.e. formation of provascular cells, xylem specification and differentiation, and phloem specification and differentiation, was compared inS. moellendorffii tissues, indicating a less complex regulatory mechanism in lycophytes than in flowering plants. The results were further strengthened by the evolutionary trend of seven transcription factor families related to vascular development, which was observed among four representative species of seed and non-seed vascular plants, and nonvascular land and aquatic plants. Conclusions The deep RNA-seq study ofS. moellendorffii discovered extensive new gene contents, including novel coding genes, lncRNAs, AS events, and refined gene models. Compared to flowering vascular plants, S. moellendorffii displayed a less complexity in both gene structure, alternative splicing, and regulatory elements of vascular development. The study offered important insight into the evolution of vascular plants, and the regulation mechanism of vascular development in a non-seed plant.